Current management issues of immediate postoperative care in pediatric kidney transplantation (Clinics, 2014)
The number of pediatric kidney transplants has been increasing in many centers worldwide, as the procedure provides long-lasting and favorable outcomes; however, few papers have addressed the immediate postoperative care of this unique population. Herein, we describe the management of these patients in the early postoperative phase. After the surgical procedure, children should ideally be managed in a pediatric intensive care unit, and special attention should be given to fluid balance, electrolyte disturbances and blood pressure control. Antibiotic and antiviral prophylaxes are usually performed and are based on the recipient and donor characteristics. Thrombotic prophylaxis is recommended for children at high risk for thrombosis, although consensus on the optimum therapy is lacking. Image exams are essential for good graft control, and Doppler ultrasound must be routinely performed on the first operative day and promptly repeated if there is any suspicion of kidney dysfunction. Abdominal drains can be helpful for surveillance in patients with increased risk of surgical complications, such as urinary fistula or bleeding, but are not routinely required. The immunosuppressive regimen starts before or at the time of kidney transplantation and is usually based on induction with monoclonal or polyclonal antibodies, depending on the immunological risk, and maintenance with a calcineurin inhibitor (tacrolimus or ciclosporin), an anti-proliferative agent (mycophenolate or azathioprine) and steroids.